2010
DOI: 10.1126/science.1193147
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Collective Intelligence Factor in the Performance of Human Groups

Abstract: Psychologists have repeatedly shown that a single statistical factor--often called "general intelligence"--emerges from the correlations among people's performance on a wide variety of cognitive tasks. But no one has systematically examined whether a similar kind of "collective intelligence" exists for groups of people. In two studies with 699 people, working in groups of two to five, we find converging evidence of a general collective intelligence factor that explains a group's performance on a wide variety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

56
1,572
12
40

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,943 publications
(1,680 citation statements)
references
References 16 publications
56
1,572
12
40
Order By: Relevance
“…Following methods used in psychology to study individual intelligence, Woolley et al [8] investigated the possibility of a collective intelligence factor: a latent factor describing a team's general ability to perform on a wide variety of tasks. They brought teams into the laboratory, had them perform a wide variety of tasks [6,9], and found that a team's performance on one type of task was closely related to its performance on all types.…”
Section: Collective Intelligencementioning
confidence: 99%
See 3 more Smart Citations
“…Following methods used in psychology to study individual intelligence, Woolley et al [8] investigated the possibility of a collective intelligence factor: a latent factor describing a team's general ability to perform on a wide variety of tasks. They brought teams into the laboratory, had them perform a wide variety of tasks [6,9], and found that a team's performance on one type of task was closely related to its performance on all types.…”
Section: Collective Intelligencementioning
confidence: 99%
“…They brought teams into the laboratory, had them perform a wide variety of tasks [6,9], and found that a team's performance on one type of task was closely related to its performance on all types. When they calculated a collective intelligence score based on the team's performance on the set of tasks, they found that it was only moderately related to the individual members' intelligence scores and was more predictive of future team performance than was individual members' average intelligence score [8] A series of studies have revealed factors related to collective intelligence, providing some insight into how to more reliably cultivate smart teams. First is the social perceptiveness of team members, or their ability to infer others' mental states, such as beliefs or feelings based on subtle cues [10].…”
Section: Collective Intelligencementioning
confidence: 99%
See 2 more Smart Citations
“…Small groups can outperform even the most skilled/knowledgeable individual on complex tasks (Woolley et al, 2010) and in remembering information . In traditional societies, social learning is usually transparent, as experts in different essential categories of adaptive knowledge (medicinal plants, hunting, fishing, cultivation) are well known to the group members .…”
Section: Social Influence: a Key Element In Decision Makingmentioning
confidence: 99%